P188 Tocilizumab for giant cell arteritis: real world experience in a single UK centre. (20th April 2020) - Reynolds, Gary; Griffiths, Bridget; Houghton, Karolyn; Thompson, Ben; Lorenzi, Alice R; Heaney, Jonathan
Abstract: Background: Tocilizumab was approved for the treatment of giant cell arteritis (GCA) by NICE in April 2018. This decision followed the GiACTA (Giant Cell Arteritis Actemra) study, a randomised control trial that demonstrated a beneficial effect of tocilizumab in reducing the frequency of disease flare and overall prednisolone requirements. However, as noted in the NICE appraisal, the extent to which the patient population in the GiACTA study reflects the population it is eventually used for in UK clinical practice is not clear. To address this, we analysed the records of all patients started on tocilizumab treatment for GCA in a single centre since its approval. Methods: We performed a retrospective analysis of the clinical records of all patients started on tocilizumab for GCA at the Freeman Hospital in Newcastle. All patients are discussed in a regional connective tissue disease MDT prior to the initiation of therapy to ensure they fulfil NICE guidelines. At each subsequent visit adverse events related to both tocilizumab and corticosteroids and any flares of GCA or ischaemic events are recorded. Results: In total 14 patients started tocilizumab since June 2018, with a cumulative exposure of 8 patient-years. The mean age was 74 years, slightly older than the average age in the GiACTA trial (69 years). In contrast to GiACTA where 48% of patients were newly diagnosed, all our patients had established disease. In our cohort 36% of patients had CT PET evidence of large vessel vasculitis, similar to the rate in GiACTA (40%) but higher than the national average of around 5%. Incidence of visual loss in our treated patients was higher at 29% than recorded in the general GCA population in the DC-VAS study (7.9%). In those treated for relapsing disease around half (56%) had recorded previous significant adverse events with steroids, including heart failure, hypertension and mood changes. Five patients had infections requiring antibiotics (cellulitis/ulcer in three, chest infection in one, urinary tract infections in two), with two serious infections requiring hospital admission (both urinary tract infections). No patients had further ischaemic events while on treatment. All patients were on a lower dose of prednisolone following treatment with an average of a 63% reduction in steroid dose. Conclusion: The modest number of patients receiving tocilizumab for GCA suggests we are not treating everyone at first relapse. The higher rates of large vessel vasculitis, visual loss and previous steroid-induced complications suggest a preference for saving tocilizumab for a more severely affected subset of patients. In this preliminary data there were reassuringly no recorded ischaemic events following treatment and steroid doses were successfully reduced in all patients. Disclosures: G. Reynolds None. B. Griffiths None. K. Houghton None. B. Thompson None. A.R. Lorenzi None. J. Heaney None.